Contributions of the tutorial education program: a study with graduates from the Conexão de Saberes em Física e Popularização da Ciência group at Unifei-Itabira - Fernandes, Brenda Martins (2020)
This work reveals the perceptions of the graduates of the Connection of Knowledge in Physics and Popularization of Science group, both from the point of view of contributions to training while graduating and professional, and to the objectives of the tutorial education program (PET). Since its creation in 2010 at Unifei-Itabira, the group has developed teaching, research and extension activities at the university and community of Itabira and region. The objective is to show qualitatively and quantitatively the contributions of PET in the graduate's life. This investigation was carried out through a survey carried out via an electronic form. The results show a high contribution regarding critical and academic education, social contribution, stimulating teaching and professional. They also show that over 90% of graduates are inserted in the labor market and 50% continue to study. The activities developed by the group contribute significantly to the training of students, develop leadership, public speaking, creativity and altruism. In addition, due to the various extension and teaching activities involving the community, the tutorial education program brings other benefits to the university, such as the university's positive exposure to society.